TECHNOLOGY FOR PEDAGOGICAL MONITORING OF STUDENTS' PHYSICAL FITNESS DURING THEIR EDUCATION - MASHARIPOV , Farhod («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
his article examines and analyzes the dynamics of growth in physical fitness, physical development, and functional status of general education students at higher education institutions during the academic year in physical education classes organized using traditional approaches. It is found that when assessing test results, modular differentiation of students based on their level of fitness is necessary.